Evaluation of the Causes of On‐Farm Harvest Losses in Canola in the Northern Great Plains. Issue 4 (1st July 2016) - Cavalieri, Andrea; Harker, K. Neil; Hall, Linda M.; Willenborg, Christian J.; Haile, Teketel A.; Shirtliffe, Steven J.; Gulden, Robert H.
Abstract : Canola ( Brassica napus L.) is the main oilseed crop grown in the northern Great Plains (Canada). This species, however, also is associated with significant seed losses before and during harvest. To determine the factors that contribute to on‐farm harvest losses in B. napus, an extensive on‐farm survey was conducted in four regions across the northern Great Plains in 2010, 2011, and 2012. In addition to measuring on‐farm harvest losses on 310 fields, a survey questionnaire was used to collect agronomic data for each field and wind data from the nearest local weather station was used to determine wind speed during the harvest season. This study showed that total on‐farm harvest losses in canola are a complex phenomenon. This study identified that managing harvest losses in B. napus begins at the time of planting. Management factors that contributed to increased yield were linked to lower proportional B. napus harvest losses. Other factors that contributed to reduced proportional harvest losses included a fungicide application at flowering, earlier windrowing and harvest dates, lower combine harvester ground speed, and reduced windrower width. Factors considered by producers as important, such as combine manufacturer or B. napus variety did not contribute significantly to total harvest losses in this crop. Nevertheless, clear management practices were identified that can be employed to minimize on‐farm harvest losses in B. napus . A better understanding of the contributions of environmental variables to harvest losses in this species is required, particularly as interest in direct‐harvesting B. napus continues to increase in western Canada.